Botulinum toxin and blink rate in patients with blepharospasm and increased blinking. Issue 3 (24th June 2014) - Ferrazzano, Gina; Conte, Antonella; Fabbrini, Giovanni; Bologna, Matteo; Macerollo, Antonella; Defazio, Giovanni; Hallett, Mark; Berardelli, Alfredo
Abstract : Objective: The aim of the study was to investigate the effect of botulinum toxin (BoNT) on blink rate (BR) in patients with blepharospasm (BSP) and increased blinking (IB). Methods: 37 patients with a clinical diagnosis of primary BSP (19 patients had tonic orbicularis oculi (OO) spasms and 18 patients had clonic OO spasms) and 8 patients with IB were included in this case-control study. All subjects underwent a standardised video protocol and clinical evaluation with a validated questionnaire designed to identify eye symptoms and Blepharospasm Disability Index (BSDI) before and 1 month after BoNT injection. BR was measured from the video recording before and after BoNT. BR in BSP and IB patients was compared with that from a group of healthy subjects and from a group of patients with hemifacial spasm (HFS). BR in HFS was also measured before and after BoNT. Results: BR was increased in patients with IB and in BSP patients with clonic spasms but not in BSP patients with tonic spasms. BoNT reduced BR in patients with IB and in patients with clonic spasms, but not in patients with tonic spasms. BoNT left BR in patients with HFS unchanged. Changes in BR after BoNT were also independent of the presence of ocular symptoms. Despite the differential response of BR, BoNT significantly reduced BSDI in patients with BSP and IB. Conclusions: BoNT differentially modulates BR in patients with BSP and IB depending on the baseline BR. BoNT injection reduces BR only when the blink generator is overactive, possibly influencing tear film retention.